Computed tomographic colonography (CTC); colorectal cancer diagnosis with CTC in an Auckland population. Issue 5 (21st May 2013) - Moore, Helen; Dodd, Nicholas
Abstract Aim To determine the sensitivity of computed tomographic colonography (CTC) in the detection of colorectal cancer in our population and evaluate the reasons why these lesions may be missed on CTC. Methods All patients who underwent CTC in the 65‐month period from 1 January 2004 to 1 July 2009 were included in the analysis. Demographic data and CTC findings were recorded, according to the CT Colonography Reporting and Data System. Data were cross‐matched with the National Cancer Registry results for colorectal cancer cases between 1 January 2004 and 1 October 2009, 3 months longer to include any delayed diagnoses. Results There were 2026 consecutive CTC patients, comprising 52.6% female, average age of 60 years; range 19–87. Approximately 84% were symptomatic. There were 45 confirmed colorectal cancers among this patient group in the National Cancer Registry during the relevant time period compared with 43 suspected cancers on CTC, giving a miss rate of 2 of 45, or 4.4%. Conclusion The sensitivity of 95% for CTC in the detection of colorectal cancer compares favourably with the published national and international data.